Rationale and pre-clinical evidences for the use of autologous cartilage micrografts in cartilage repair - Marco Viganò; Irene Tessaro; Letizia Trovato; Alessandra Colombini; Marco Scala; Alberto Magi; Andrea Toto; Giuseppe Peretti; Laura de Girolamo (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background The management of cartilage lesions is an open issue in clinical practice, and regenerative medicine represents a promising approach, including the use of autologous micrografts whose efficacy was already tested in different clinical settings. The aim of this study was to characterize in vitro the effect of autologous cartilage micrografts on chondrocyte viability and differentiation and perform an evaluation of their application in racehorses affected by joint diseases. Materials and methods Matched human chondrocytes and micrografts were obtained from articular cartilage using Rigenera® procedure. Chondrocytes were cultured in the presence or absence of micrografts and chondrogenic medium to assess cell viability and cell differentiation. For the pre-clinical evaluation, three racehorses affected by joint diseases were treated with a suspension of autologous micrografts and PRP in arthroscopy interventions. Clinical and radiographic follow-ups were performed up to 4 months after the procedure. Results Autologous micrografts support the formation of chondrogenic micromasses thanks to their content of matrix and growth factors, such as transforming growth factor β (TGFβ) and insulin-like growth factor 1 (IGF-1). On the other hand, no significant differences were observed on the gene expression of type II collagen, aggrecan, and SOX9. Preliminary data in the treatment of racehorses are suggestive of a potential in vivo use of micrografts to treat cartilage lesions. Conclusion The results reported in this study showed the role of articular micrografts in the promoting chondrocyte differentiation suggesting their potential use in the clinical practice to treat articular lesions.